1998
DOI: 10.1128/jcm.36.3.662-668.1998
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intimins α, β, γ, and δ, Four Intimin Derivatives Expressed by Attaching and Effacing Microbial Pathogens

Abstract: Intimins are outer membrane proteins expressed by enteric bacterial pathogens capable of inducing intestinal attachment-and-effacement lesions. A eukaryotic cell-binding domain is located within a 280-amino-acid (Int280) carboxy terminus of intimin polypeptides. Polyclonal antiserum was raised against Int280 from enteropathogenicEscherichia coli (EPEC) serotypes O127:H6 and O114:H2 (anti-Int280-H6 and anti-Int280-H2, respectively), and Western blot analysis was used to explore the immunological relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 273 publications
(130 citation statements)
references
References 49 publications
(56 reference statements)
4
120
0
6
Order By: Relevance
“…Tir binds to the Cterminus of the intimin molecule (Liu et al, 1999;Luo et al, 2000), the amino-acid sequence of which varies between AE organisms. Four principal subtypes of intimin (a, b, g and 3) have been established, based on antigenic, amino-acid and eae sequence differences at the C-terminus domain (Adu-Bobie et al, 1998;Oswald et al, 2000). However, up to seven further subtypes have been proposed, based upon eae sequence variation (Zhang et al, 2002;Jores et al, 2003).…”
Section: Stage 3: Intimate Attachmentmentioning
confidence: 99%
“…Tir binds to the Cterminus of the intimin molecule (Liu et al, 1999;Luo et al, 2000), the amino-acid sequence of which varies between AE organisms. Four principal subtypes of intimin (a, b, g and 3) have been established, based on antigenic, amino-acid and eae sequence differences at the C-terminus domain (Adu-Bobie et al, 1998;Oswald et al, 2000). However, up to seven further subtypes have been proposed, based upon eae sequence variation (Zhang et al, 2002;Jores et al, 2003).…”
Section: Stage 3: Intimate Attachmentmentioning
confidence: 99%
“…Although the intimin C-terminal portion interacts with Tir, it has been suggested that the different intimin subtypes may drive bacteria to different intestinal regions (Phillips & Frankel, 2000). Thus far, eae variant alleles encoding 33 different intimin subtypes have been established (reviewed in Schmidt, 2010), with subtypes alpha, beta, and gamma being the most common (Adu-Bobie et al, 1998;Beutin et al, 2003;Ramachandran et al, 2003;Blanco et al, 2006a, b;Abe et al, 2009;Horcajo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, eae from a dog EPEC [13] and a bovine EHEC [14] have likewise been cloned and sequenced. The eae gene variants of human strains have been recently classi¢ed as K, L, Q and O ( [15], Oswald, personal communication). They can be distinguished by PCR or gene probes [15].…”
Section: Introductionmentioning
confidence: 99%